Comparison of Life History Characteristics of the Genetically Modified OX513A Line and a Wild Type Strain of Aedes aegypti - Bargielowski, Irka; Nimmo, Derric; Alphey, Luke; Koella, Jacob C (My University, 2011)
The idea of implementing genetics-based insect control strategies modelled on the traditional SIT (Sterile Insect Technique), such as RIDL (Release of Insects carrying a Dominant Lethal), is becoming increasingly popular. In this paper, we compare a genetically modified line of Aedes aegypti carrying a tetracycline repressible, lethal positive feedback system (OX513A) with a genetically similar, unmodified counterpart and their respective responses to increasing larval rearing density using a constant amount of food per larva. The parameters that we examined were larval mortality, developmental rate (i.e., time to pupation), adult size and longevity. Analysis revealed some statistically significant differences between the life history traits we examined. The genetically modified OX513A line overall showed 5% lower larval survival as well as reduced adult longevity (20 vs 24 days mean lifespan) compared to the unmodified line. Furthermore, the OX513A line pupated about one day sooner, which could be advantageous in mass-rearing, but produced somewhat smaller adults than the unmodified line; this effect was more pronounced in females than in males. Increasing the larval rearing density delayed pupation, decreased adult longevity and reduced adult size in both lines. While the delay in pupation and the decrease in longevity were similar between the two lines, the decrease in adult size was more pronounced for OX513A males. Our study shows that in a controlled laboratory situation the transgenic sterile OX513A line may have somewhat reduced performance compared to its unmodified counterpart and that high rearing densities may further reduce performance. Laboratory-based cage trials as well as field trials are necessary to assess how the differences in life history traits documented here impact the males' success upon release. Furthermore, this paper highlights the potential value of optimisation of mass-rearing systems as optimised rearing methods may be able to alleviate performance issues associated with specific lines or with lab-adapted lines in general.